Observing The Effect of Guided Inquiry Learning and Students'Spatial Ability toward The Students' Learning Outcome on Molecular Geometry Content - Nur Sa'adah; Effendy Effendy; Suhadi Ibnu (Universitas Negeri Malang, 2017)
Abstract: The purpose of this study were: (1) to know the  differences of learning achievment on the  molecular shape subject between the students who  taught by inquiry learning and verification (2) to know the  differences betwen the high spatial ability to the students learning achievement in the molecular shape topic (3) to know the interaction between the  inquiry learning and verification teaching with the students' spatial ability. The results showed that: (1) there were differences in learning achievment of students who were taught by inquiry learning and verification. The students' learning achievment of students who were taught by inquiry learning better than students who were taught by verification (2) there were differences between in learning outcomes of students with high spatial and students with low spatial, students who have high spatial performance is better than low spatial ability students the high spatial ability to the students learning achievement in the molecular shape topic (3) there were not  interaction between  inquiry learning and verification methods  with the students' spatial ability. Key Words: inquiry learning, visibility space, learning achievment     Abstrak: Tujuan dari penelitian ini adalah: (1) mengetahui apakah ada perbedaan hasil belajar pada pokok bahasan bentuk molekul antara siswa yang diajar dengan pendekatan inkuiri terbimbing dan pendekatan verifikasi (2) mengetahui apakah terdapat perbedaan antara kemampuan kemampuan pandang ruang tinggi dan rendah terhadap hasil belajar siswa (3). mengetahui apakah terdapat interaksi antara cara pengajaran Inkuiri terbimbing dan verifikasi dengan kemampuan pandang ruang siswa.. Hasil penelitian menunjukkan bahwa : (1) ada perbedaan hasil belajar siswa yang diajar dengan cara inkuiri terbimbing dan verifikasi. Hasil belajar siswa yang diajar dengan cara inkuiri terbimbing lebih baik dibanding dengan siswa yang diajar dengan cara verifikasi (2) ada perbedaan kemampuan pandang ruang tinggi dan rendah terhadap prestasi belajar kimia pada bentuk molekul, hasil belajar kimia dipengaruhi oleh kemampuan pandang ruang siswa (3) tidak ada interaksi antara metode pembelajaran inkuiri terbimbing dan verifikasi dengan kemampuan pandang ruang siswa. Kata kunci: pendekatan inkuiri terbimbing, kemampuan pandang ruang, hasil belajar